KEBUTUHAN HIDUP LAYAK DAN PENGARUHNYA TERHADAP PENETAPAN UPAH MINIMUM PROVINSI DITINJAU DARI HUKUM KETENAGAKERJAAN - Syarifa Mahila (Universitas Batanghari Jambi, 2014)
Wages are the most vulnerable in industrial relations. Life Components (KHL) as the basis for the determination of the minimum wage is an increase of the minimum living needs. Provincial Minimum Wage (UMP) is the applicable minimum wage for all districts / municipalities in the province. The minimum wage is set annually by the Governor upon the recommendation of provincial councils. Provincial minimum wage not later than 60 days before the date of enactment of the minimum wage, which is January 1,Keywords: Living Needs, Provincial Minimum Wage Fixing.